Practice patterns amongst fetal centers performing intrauterine transfusions (PACT): An international survey study. (July 2022) - Donepudi, Roopali; Antolin, Eugenia; Molina, Francisca; Sananes, Nicolas; Khalil, Asma; Abbasi, Nimrah; Sánchez-Durán, M.A.; Hecher, Kurt; Fabietti, Isabella; Jouannic, Jean-Marie; Ortiz, Javier U.; Borrell, Antoni; et al.
Highlights: Intrauterine fetal transfusion to treat fetal anemia, has been performed by intraperitoneal, intravascular or a combination of approaches. Complications from these procedures have reduced significantly over the years. This is the first study to assess fetal transfusion protocols in experienced fetal centers. Standardized protocols and physician experience improve outcomes, understanding the different practice patterns helps identify the ideal approach and improve patient care. Abstract: Objectives: Fetal anemia secondary to incompatibility between maternal-fetal blood types can result in hydrops and demise. Intrauterine transfusions have improved survival in experience centers. Our objective was to determine the practice patterns amongst fetal centers. Study Design: Thirteen fetal centers across the world were surveyed. Results from all participating centers were recorded, analyzed, and presented as ratios. Questions on the survey were related to experience of the physician, preferred methods of transfusion, fetal surveillance, and timing of delivery. Results: Differences amongst centers were as follows: 54% of the centers performed transfusions in operating room, the remaining did them in a clinic room or close to the operating room; 31% did not use maternal anesthesia, 31% used oral or intravenous sedation and 38% used a combination of local with oral or intravenous sedation. The similarities include: 84% performed intravenous transfusions, while 2 centers reported intraperitoneal and intracardiac transfusions were performed for very early cases; 85% of centers performed the last transfusion at 34–35 weeks and 77% electively delivered their patients at 37 weeks. Conclusion: Method of transfusion and delivery timing was similar in most centers; however, differences were seen in location of procedure, anesthetic coverage, and surveillance. Further assessment is needed to determine if these differences in practice have any potential neonatal effects.